Giant Basal Cell Carcinomas Express Neuroactive Mediators and Show a High Growth Rate: A Case–Control Study and Meta-Analysis of Etiopathogenic and Prognostic Factors. (March 2017) - Yazdani Abyaneh, Mohammad-Ali; Engel, Peter; Slominski, Andrzej; Ragsdale, Bruce; Agag, Richard; Cramer, Daniel; Carlson, J. Andrew
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Giant basal cell carcinomas (GBCCs), (BCC ≥ 5 cm), are often painless, destructive tumors resulting from poorly understood patient neglect. Objectives: To elucidate etiopathogenic factors distinguishing GBCC from basal cell carcinoma (BCC) and identify predictors for disease-specific death (DSD). Methods: Case–control study examining clinicopathologic and neuroactive factors (β-endorphin, met-enkephalin, serotonin, adrenocorticotropic hormone, and neurofilament expression) in GBCC and BCC. Systematic literature review to determine DSD predictors. Results: Thirteen GBCCs (11 patients) were compared with 26 BCCs (25 patients). GBCC significantly differed in size, disease duration, and outcomes; patients were significantly more likely to live alone, lack concern, and have alcoholism. GBCC significantly exhibited infiltrative/morpheic phenotypes, perineural invasion, ulceration, and faster growth. All neuromediators were similarly expressed. Adenoid phenotype was significantly more common in GBCC. Adenoid tumors expressed significantly more β-endorphin (60% vs. 18%, P = 0.01) and serotonin (30% vs. 4%, P = 0.02). In meta-analysis (n ≤ 311: median age 68 years, disease duration 90 months, tumor diameter 8 cm, 18.4% disease-specific mortality), independent DSD predictors included tumor diameter (cm) (hazard ratio (HR): 1.12, P = 0.003), bone invasion (HR: 4.19, P = 0.015), brain invasion (HR: 8.23, P = 0.001), and distant metastases (HR: 14.48, P = 0.000). Conclusions: GBCC etiopathogenesis is multifactorial (ie, tumor biology, psychosocial factors). BCC production of paracrine neuromediators deserves further study.